2019
DOI: 10.3889/oamjms.2019.848
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular comorbidity in patients with chronic obstructive pulmonary disease: echocardiography changes and their relation to the level of airflow limitation

Abstract: Objective. To compare frequency of echocardiographic changes in patients with chronic obstructive pulmonary disease (COPD) and non-COPD controls and to assess their relation to the level of airflow limitation. Methods. Study population included 120 subjects divided in two groups. Group 1 included 60 patients with COPD (52 male and 8 female, aged 40 to 80 years) initially diagnosed according to the actual recommendations. Group 2 included 60 subjects in whom COPD was excluded serving as a control. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…This is finding corroborates with the study of Scott, Spodick et al [20][21][22] Buklioska-Ilievska has reported that Frequency of echocardiographic changes in COPD patients increases with the severity of airflow obstruction which supports our study. 23 In our study right ventricular hypertrophy pulmonary hypertension and right ventricular failure are common in sever COPD patients, which is supported by the work of Freixa et al 24…”
Section: Resultssupporting
confidence: 86%
“…This is finding corroborates with the study of Scott, Spodick et al [20][21][22] Buklioska-Ilievska has reported that Frequency of echocardiographic changes in COPD patients increases with the severity of airflow obstruction which supports our study. 23 In our study right ventricular hypertrophy pulmonary hypertension and right ventricular failure are common in sever COPD patients, which is supported by the work of Freixa et al 24…”
Section: Resultssupporting
confidence: 86%
“…The reduction of FEV1 in COPD patients increases the risk of fatal cardiovascular and non-fatal coronary events 10 . Electrocardiography can be a practical tool for the early diagnosis of any cardiac alterations related to COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the right ventricular dimension and right ventricular dimension index were higher in the severe and very severe COPD group, this difference did not reach statistical significance. This may be due to the adaptive mechanisms in the chronic process in patients with COPD 10,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the RV evaluation in patients with COPD should not be limited to sPAP evaluation. In fact, increased sPAP values at rest are a sign of advanced pulmonary circulation impairment [22].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%